Quantitative Evaluation of Draught Survey Through Correlation Test of Quarter Mean: A Case Study on a Coal Bulk Carrier - Denny Murdany Muchsin; Rahmad Setya Darmawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Complicated draught survey activities both at the data collection stage and the calculation stage, especially at sea, make it difficult for surveyors to accurately inform coal cargo volumes. However, in practice, most coal bulk-carrier surveyors can provide precise information on coal cargo volumes between ports up to a difference of less than 0.5%. This difference is not enough to be used as the only parameter in supervising draught survey activities. More effective monitoring needs to be done so that data reliability can be validated. This study aims to propose a new method of off-site surveillance of draught survey activities through correlation tests with a case study on a bulk-carrier ship less than 10 years old in all coal shipments at one of coal-fired power plant during year 2021. The results of the study show that based on the correlation test of Pearson (2-tailed), Spearman (2-tailed), and Kendall (2-tailed), during coal shipments in 2021 both at loading ports and at unloading ports, the interpretation of the quarter-mean as independent variable is at least strongly correlated with both displacement and displacement corrected for density, while the correlation of quarter mean with both net displacement and constant is not significant (negligible).